Arsenic contaminated drinking water and nutrition status of the rural communities in Bagahi village, Rautahat district, Nepal - Pradhan, B (Journal of Institute of Medicine Nepal, 2007)
Background: Groundwater is the main source of drinking water in the Tarai region of Nepal. Analysis of arsenic contaminated groundwater of 287 tube wells and nutrition level of the rural communities of Bagahi village, Rautahat district, Tarai region has been performed. Methods: Altogether 538 households have access to the tube wells’ water for consumption. Results: About 6% of the total tested tube wells are considered as risk tube wells, which have arsenic level above the Nepal Interim Standard 50 part per billion (ppb). Of the total risk population, about 9% have been identified as arsenicosis patients. About 80% risk populations have consumed inadequate nutrition in terms of calorie content. The risk of arsenic among the risk populations is high because they are in most cases under nutrition and consuming the contaminated water. Conclusion: This indicates that the rural communities of the Bagahi locality are facing alarming situation. Immediate measures to mitigate the problem are warranted. Key words: Arsenic, nutritional status, rural community, Rautahat district The full text of this paper is available at Journal of Institute of Medicine website